2011
DOI: 10.1590/s1519-69842011000300011
|View full text |Cite
|
Sign up to set email alerts
|

Edge effects on fern community in an Atlantic Forest remnant of Rio Formoso, PE, Brazil

Abstract: We have investigated how edge effects influence the fern community of Jaguarão Forest (08º 35' 49" S and 35º 15' 39" W), located in the district of Rio Formoso, Pernambuco, Brazil. A comparative analysis was made of the interior and edge of the fragment of forest, regarding the richness, abundance and diversity of ferns in the two areas. Six plots of 10 × 20 m were chosen, three in each area. A total of 381 ferns were recorded, which were distributed among 25 species, 17 genera and 12 families. The two areas (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 34 publications
3
20
1
9
Order By: Relevance
“…Nevertheless, it was observed that the edge effect was stronger in Cravina, where the species richness reduced to half, compared with Macaco Branco, suggesting that an agricultural matrix enhances the edge effect. The current study therefore provides further evidence supporting the findings of Paciencia & Prado (2004), Silva et al (2011), andSilva et al (2014), indicating that ferns and lycophytes are potentially vulnerable to edge effects.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Nevertheless, it was observed that the edge effect was stronger in Cravina, where the species richness reduced to half, compared with Macaco Branco, suggesting that an agricultural matrix enhances the edge effect. The current study therefore provides further evidence supporting the findings of Paciencia & Prado (2004), Silva et al (2011), andSilva et al (2014), indicating that ferns and lycophytes are potentially vulnerable to edge effects.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, in a remnant of Atlantic rainforest in northeastern Brazil, other authors observed that temperatures were higher at forest edges (Silva et al 2011). Although some authors (Lovejoy et al 1986;Kapos 1989;Murcia 1995;Laurance 1997) suggest that air temperature is one of the most decisive factors for edge effects to occur, evidence to support this fact was not found in this study.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations